2021
DOI: 10.1038/s41467-021-23680-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the biogenesis pathway and dynamics of thylakoid membranes

Abstract: How thylakoid membranes are generated to form a metabolically active membrane network and how thylakoid membranes orchestrate the insertion and localization of protein complexes for efficient electron flux remain elusive. Here, we develop a method to modulate thylakoid biogenesis in the rod-shaped cyanobacterium Synechococcus elongatus PCC 7942 by modulating light intensity during cell growth, and probe the spatial-temporal stepwise biogenesis process of thylakoid membranes in cells. Our results reveal that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…It has been clearly shown almost 40 years ago [7][8][9] that, in higher plants, PSII is mainly present in TM regions called grana (stacked TM areas), while PSI is found in stroma lamellae (unstacked TM areas). A similar grana/stroma-like heterogeneity has been recently identified also in cyanobacteria [1], in line with several other works showing spatial variability in PPC localization in thylakoids [10][11][12][13][14]. In the work of Strašková and co-workers [1], a functional analogy between granal/stromal thylakoid of higher plants TM and so-called photosynthetic microdomains (MDs) in cyanobacteria has been proposed.…”
Section: Introductionsupporting
confidence: 82%
“…It has been clearly shown almost 40 years ago [7][8][9] that, in higher plants, PSII is mainly present in TM regions called grana (stacked TM areas), while PSI is found in stroma lamellae (unstacked TM areas). A similar grana/stroma-like heterogeneity has been recently identified also in cyanobacteria [1], in line with several other works showing spatial variability in PPC localization in thylakoids [10][11][12][13][14]. In the work of Strašková and co-workers [1], a functional analogy between granal/stromal thylakoid of higher plants TM and so-called photosynthetic microdomains (MDs) in cyanobacteria has been proposed.…”
Section: Introductionsupporting
confidence: 82%
“…Liberton et al [ 138 ] found through serial sectioning and electron tomography that the thylakoids form a completely independent membrane system from the plasma membrane. However, the thylakoid sheets do converge at certain cellular locations near the plasma membrane [ 139 , 140 , 141 , 142 ]. Whether these convergence zones are connected to the plasma membrane is debated, but they have been proposed to be the site of PSII biogenesis and/or repair [ 34 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…An interesting study on the biogenesis of cyanobacterial thylakoid membranes was recently published ( Huokko et al, 2021 ), in which it was shown that the assembly of photosynthetic membrane complexes respond dynamically to changing light strength. The assembly of PSI complexes in cyanobacterial cells are largely improved during a 5-day dark adaptation period.…”
Section: Higher Order Oligomersmentioning
confidence: 99%